2017
DOI: 10.18201/ijisae.2017533901
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Cervical Disc Herniation Disease using Muscle Fatigue based surface EMG signals by Artificial Neural Networks

Abstract: This study presents the classification of cervical disc herniation patients and healthy persons by using muscle fatigue information. Cervical disc herniation patients suffer from neck pain and muscle fatigue in the neck increases these aches. Neck pain is the most common pain type encountered after back pain. The discomforts that occur in the neck region affect the daily quality of life, so the number of researches done in this area is increasing. In this study surface Electromyography (EMG) signals were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…To answer this question, an experimental study was performed. Detailed information about the experimental study can be found in [22], but the present study only addresses the resting state data recorded from the trapezius muscle. In this prospective study, sEMG data were collected by a physician and a technician in the neurology department of Selcuk College Faculty of Medicine using surface electrodes and a Neoropack Nihon Kohden EMG device in 10 CDH patients (8 males and 2 females, aged 17 to 67 years) and 10 healthy volunteers (4 males and 6 females, aged 19 to 48 years).…”
Section: Data Set and Data Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…To answer this question, an experimental study was performed. Detailed information about the experimental study can be found in [22], but the present study only addresses the resting state data recorded from the trapezius muscle. In this prospective study, sEMG data were collected by a physician and a technician in the neurology department of Selcuk College Faculty of Medicine using surface electrodes and a Neoropack Nihon Kohden EMG device in 10 CDH patients (8 males and 2 females, aged 17 to 67 years) and 10 healthy volunteers (4 males and 6 females, aged 19 to 48 years).…”
Section: Data Set and Data Preparationmentioning
confidence: 99%
“…In the literature, some studies classify neuromuscular diseases [10][11][12], detect muscle activity [13][14], muscle fatigue [15][16], and classification of low back pain [17][18] and neck pain [19][20][21] using sEMG. To our knowledge, no study classifies CDH patients using surface EMG, except [22]. In addition, some studies draw attention to the upper trapezius muscle during semi-static activities that require repetitive movements of the upper extremity.…”
Section: Introductionmentioning
confidence: 99%